THE REPRESENTATION OF MULTICULTURAL VALUES IN NUSSA: THE MOVIE - Hariadi, Rizki; Asih, Yuni Utami; Suhatmady, Bibit (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Nussa: The Movie is present in the midst of the lack of entertainment with education and multicultural values. Indonesian children and parents need to be provided with entertainment with this content. The researcher displays the multicultural values contained in the film in qualitative descriptive research using the Critical Discourse Analysis method by Norman Fairclough. As a result, there are several multicultural values contained in the film, primary Islam and Indonesian culture in general and particularly local cultural values, that are; Betawi, Batak, and Javanese.